Microstructure and textural and viscoelastic properties of model processed cheese with different dry matter and fat in dry matter content - Černíková, Michaela; Nebesářová, Jana; Salek, Richardos Nikolaos; Řiháčková, Lada; Buňka, František (Journal of dairy science, 2017)
The aim of this work was to examine the effect of a different dry matter (DM) contents (35 and 45% wt/wt) and fat in DM contents (40 and 50% wt/wt) on the textural and viscoelastic properties and microstructure of model processed cheeses made from real ingredients regularly used in the dairy industry. A constant DM content and constant fat in DM content were kept throughout the whole study. Apart from the basic chemical parameters, textural and viscoelastic properties of the model samples were measured and scanning electron microscopy was carried out. With increasing DM content, the rigidity of the products increased and the size of the fat globules in the model samples of the processed cheeses decreased. With increasing fat in DM content, the rigidity of the processed cheeses decreased and the size of the fat globules increased.
Keywords: lipidová tělíska; scanning electron microscopy; Animals; viskozita; glykolipidy; pružnost; texture; Cheese; Food Handling; rheology; Elasticity; Glycoproteins; processed cheese; mikroskopie elektronová rastrovací; Lipid Droplets; Glycolipids; glykoproteiny; zvířata; Viscosity; manipulace s potravinami; sýr; Microscopy, Electron, Scanning